Effect of strength, aerobic, and concurrent training on the memory of cognitively preserved older adults: a randomized clinical trial protocol - Nadyne Rubin; Eduarda Blanco-Rambo; Marcelo Bandeira Guimarães; Caroline Rosa Muraro; Rose Löbell; Nadja Schröder; Elke Bromberg; Irani Argimon; Eduardo Lusa Cadore; Caroline Pietta-Dias (Brazilian Society of Geriatrics and Gerontology, 2024)
Objectives: To verify the effect of strength, aerobic, and concurrent training on the memory of cognitively preserved older adults. Methods: A randomized controlled clinical trial will be conducted. Sedentary older adults (aged 60 to 75 years) of both genders will participate. Outcome measures will include blood biomarkers, cognitive tests, depressive symptoms, socioeconomic data, and physical assessments. Participants will be randomized into the following groups: strength training, aerobic training, concurrent training, or control. Interventions will be conducted for 12 weeks, with adherence to training sessions monitored. Pre-training values will be compared between groups using a one-way ANOVA test. Training effects will be evaluated through two-way ANOVA (time × group). The research protocol was registered in The Brazilian Registry of Clinical Trials (ReBEC) (RBR-655vxdd). Expected results: We believe that concurrent training may yield greater efficacy in improving memory outcomes, combining the benefit of both training modalities. Relevance: Considering the increase in population aging and that few studies have evaluated the chronic effect ofphysical exercise on the memory of cognitively preserved older adults, this is a relevant topic, since much of the literature has focused on investigating older adults with some cognitive decline. Furthermore, our aim is to provide an alternative training option by combining the benefits of aerobic and strength training, thereby optimizing time and enhancing both physical capacity and memory.